PEMANFAATAN MULTIMEDIA INTERAKTIF DALAM APLIKASI MOBILE UNTUK PENGENALAN CAGAR BUDAYA PEMALANG - DIDI PURNOMO; Aprilia, Ari Maulidia; Turmudi, Ahmad (Universitas Islam Syekh Yusuf Tangerang, 2025)
he lack of public awareness—especially among younger generations—regarding the importance of cultural heritage preservation presents a major challenge in the digital era. This study aims to develop and evaluate the effectiveness of an educational mobile application based on interactive multimedia to introduce cultural heritage in Pemalang Regency. The application,